Enrobing Ceremony for Judges Thomas Harris, Steven Vartabedian, Edward Sarkisian, Jr. and Lawrence Jones at Fresno's Veterans Memorial Auditorium - Watkins, Howard::::::::: (1987)
Judges Stephen Vartabedian, Thomas Harris, Stephen Henry, John "Nip" Gallagher, Lawrence Jones and Edward Sarkisian, Jr.